1998
DOI: 10.1161/01.res.82.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Cell Replication in the Arterial Wall

Abstract: This study examined intracellular signal events of arterial cells following balloon catheter injury to rat carotid artery. Within 30 minutes, a marked increase in extracellular signal-regulated kinase-1/2 (ERK1/2) activity was observed. This activity remained elevated for 12 hours but had decreased to control levels by day 1. No increase in ERK1/2 was detected at any later times. Injection of anti-fibroblast growth factor 2 antibody (60 mg i.v.) significantly inhibited the activation of ERK1/2 at 30 minutes af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…In mice treated with sRAGE, however, no suppression of phosphorylation of Erk1/2 or PKB was observed ( Figure 4, c and d). Previous work has shown that pharmacologic blockade of mitogenactivated protein kinase-1 or PI3K suppressed an early phase of medial cell proliferation, but was without effect on intimal proliferation, the latter contributing centrally to restenosis in rodent models (42,43). A recent study, however, demonstrated activation of Jak2 and Stat3 (as well as more transient activation of Stat1) following arterial injury (45).…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…In mice treated with sRAGE, however, no suppression of phosphorylation of Erk1/2 or PKB was observed ( Figure 4, c and d). Previous work has shown that pharmacologic blockade of mitogenactivated protein kinase-1 or PI3K suppressed an early phase of medial cell proliferation, but was without effect on intimal proliferation, the latter contributing centrally to restenosis in rodent models (42,43). A recent study, however, demonstrated activation of Jak2 and Stat3 (as well as more transient activation of Stat1) following arterial injury (45).…”
Section: Figurementioning
confidence: 96%
“…phase of cellular proliferation in the repairing arterial segment (42,43). To study these cascades, phosphorylation of Erk1/2 and protein kinase B (PKB), the latter a downstream target of PI3K (44), was assessed.…”
Section: Figurementioning
confidence: 99%
“…The ERK1/2 pathway is a tyrosine kinase-dependent pathway normally stimulated by growth factor receptors that are involved in cell growth, proliferation and differentiation. Ang II also activates c-src dependent mechanism 16) and c-src was suggested to control VSMCs proliferation 17) and vascular contraction. 18) Treatment with an MEK-1 inhibitor PD98059 reduced Ang II-induced high blood pressure in vivo 19) and prevented the contractile effects of Ang II in isolated resistance arteries in vitro.…”
Section: Isoproterenol Induces Ho-1 Expression Through B B 2 -Adrenocmentioning
confidence: 99%
“…7) Using balloon injured carotid artery, it was demonstrated that MAPK signaling, especially ERK1/2, is increased and that medial cell replication following injury is reduced by PD098059. 13) ERK1/2 (a MAPK family member) plays a central role on cell growth regulation, and recently this pathway was found to be involved by triggering Ras-Raf activation, MEK phosphorylation, and ERK1/2 phosphorylations in the proliferative effect of PDGF-BB in VSMCs. 6,7,11,14) As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%